CLINICAL, DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE OF CYTOKINE INDICATORS IN PRIMARY AND RECURRENT STENOSING LARYNGOTRACHEITIS IN CHILDREN - Sh.U. Samieva; F.O. Olimjanova; Z.O. Olimjanova (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
In recent years, against the background of the growing incidence of acute respiratory viral infections (ARVI), acute stenosing laryngotracheitis of viral etiology has attracted special attention from pediatricians and pediatric otolaryngologists. The frequency of such diseases, according to various studies, varies from 0.1% to 0.4% among all hospitalized children diagnosed with acute respiratory viral infection (ARVI). The development of stenosing laryngotracheitis in ARVI significantly worsens the condition of patients, the symptoms of this disease predominate in the clinical picture, and in some cases, the child's life depends on its outcome.